The Role of Brand Awareness in Mediating the Influence of Digital Marketing and Digital Content Quality on Increasing Sales of Culinary MSMEs (Case Study in Panam, Pekanbaru) - Kurnia, Dedi; Akbar, Rahmad; Yetti, Dzulhijjah; Sispurwanto, Yedi; Nofiar. Am, Andri (Journal of Engineering Science and Technology Management, 2025)
This study aims to analyze and understand the role of brand awareness as a mediator in the relationship between digital marketing strategies and digital content quality on the sales growth of culinary MSMEs in Panam, Pekanbaru. The research employs a quantitative approach using Path Analysis. Data were collected randomly from culinary MSMEs in Panam, Pekanbaru, over the period from 2020 to 2024. Data analysis techniques include descriptive analysis, normality test, multicollinearity test, autocorrelation test, and heteroskedasticity test. The findings of the study are as follows: 1) Digital marketing strategies have a positive and significant impact on brand awareness of culinary MSMEs. 2) Digital content quality has a positive and significant impact on brand awareness of culinary MSMEs. 3) Digital marketing strategies have a positive and significant impact on the sales growth of culinary MSMEs. 4) Digital content quality has a positive and significant impact on the sales growth of culinary MSMEs. 5) Brand awareness has a positive and significant impact on the sales growth of culinary MSMEs. 6) Digital marketing strategies significantly enhance sales growth through the mediation of brand awareness in culinary MSMEs. 7) Digital content quality significantly enhances sales growth through the mediation of brand awareness in culinary MSMEs.